Digital Generation and Teachers - Geladze, Darejan; Motskobili, Ia; Meskhidze, Shorena (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
Digital technologies have created a new digital era, on the basis of which the information sought appears as a treasure in today's life, and information technologies are the main indicator of the country's development. The creation of global information systems in the world is proceeding rapidly and the goal is to make the provision of information in the Internet space to any interested person in real time reliable. Modern technologies allow the teacher to conduct the learning process interactively and interestingly, to make free and easy-to-use digital tools accessible and understandable to everyone, for which only a computer system and an Internet connection are required, while inappropriate use is accompanied by challenges and threats, in particular, the lack of information literacy, information search, factors related to distribution and use, personal data infringement, etc. When interacting with the digital world, it is important for a modern teacher to have the necessary competencies for the safe and ethical use of information and communication technologies, which makes him a digital citizen.